Post-service analysis of the degradation and protective mechanisms of chromate-based structural aircraft coatings - Cornet, A.J.; Homborg, A.M.; Hoen - Velterop, L. 't; Mol, J.M.C. (Elsevier, 2024)
The substitution of chromate-containing structural coating systems in aviation with alternatives complying with nowadays strict environmental, health and safety regulations remains a formidable challenge. This complexity is partly due to the absence of a standardized from-test-to-market methodology, including a performance comparison between chromate-containing and alternative coating systems. To address this gap, the present study delves into the identification of crucial degradation factors that merit inclusion in such a methodology. Concurrently, it investigates the protective mechanisms inherent in chromate-containing coating systems and proposes improvements that can be applied to alternative coating systems. This study entails a comprehensive post-service examination of the degradation of paint applied to an aircraft component with over 35 years of service, employing electrochemical, microscopic and spectroscopic techniques. The findings underscore the role of thermo-oxidation as a significant degradation factor in the aging process of such coatings. Furthermore, the investigation elucidates a notable phenomenon in which aluminium ions within the coating pores form an aluminium hydroxide gel onto which chromate adsorbs. This process contributes to an increase in pore resistance upon exposure to electrolyte, leading to a self-healing barrier effect within the coating. Remarkably, this self-healing mechanism continues to offer long-term protection even when the coating matrix is sub-optimally cured due to application errors. Furthermore, this study reveals that the significant changes in capacitance during immersion testing result primarily from inhibitor leaching, emphasizing the effectiveness of combining Electrochemical Impedance Spectroscopy (EIS) with Scanning Electron Microscopy (SEM) analysis for studying coating degradation.